2011
DOI: 10.1176/appi.ajp.2010.10050755
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacogenetic Approach at the Serotonin Transporter Gene as a Method of Reducing the Severity of Alcohol Drinking

Abstract: Objective-Severe alcohol consumption can cause serious morbidity and death. Because the serotonin transporter (5-HTT) is an important regulator of neuronal 5-HT function, allelic differences at that gene may modulate the severity of alcohol consumption and predict therapeutic response to the 5-HT 3 receptor antagonist, ondansetron.Method-We randomized 283 alcoholics by genotype in the 5′-regulatory region of the 5-HTT gene (LL/LS/SS), with additional genotyping for another functional single nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
145
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(156 citation statements)
references
References 56 publications
9
145
0
2
Order By: Relevance
“…Specifi cally, in individuals with the L A L A genotype, sertraline decreased drinking signifi cantly in late-onset alcoholics, whereas in early-onset alcoholics, placebo treatment was associated with fewer drinking and heavy drinking days. Johnson et al (2011) subsequently found that variants in SLC6A4 infl uenced the response to ondansetron: The medication reduced drinking only in alcohol-dependent individuals with the 5-HTTLPR LL genotype. Further, a single nucleotide polymorphism in the 3´ untranslated region (3´UTR) of the serotonin transporter gene (Seneviratne et al, 2009) interacted with the 5-HTTLPR polymorphism to moderate the response to ondansetron.…”
Section: Pharmacogenetic Approachesmentioning
confidence: 99%
“…Specifi cally, in individuals with the L A L A genotype, sertraline decreased drinking signifi cantly in late-onset alcoholics, whereas in early-onset alcoholics, placebo treatment was associated with fewer drinking and heavy drinking days. Johnson et al (2011) subsequently found that variants in SLC6A4 infl uenced the response to ondansetron: The medication reduced drinking only in alcohol-dependent individuals with the 5-HTTLPR LL genotype. Further, a single nucleotide polymorphism in the 3´ untranslated region (3´UTR) of the serotonin transporter gene (Seneviratne et al, 2009) interacted with the 5-HTTLPR polymorphism to moderate the response to ondansetron.…”
Section: Pharmacogenetic Approachesmentioning
confidence: 99%
“…Clinical studies, however, demonstrated that serotonergic medications-the most studied of which are the SSRIs-have only a modest, inconsistent effect on drinking behavior (Kranzler and Anton, 1994). The 5-HT 3 (5-hydroxytryptamine-3) antagonist, ondansetron, has also been studied for this purpose (Johnson et al, 2000(Johnson et al, , 2011.…”
Section: Medications That Directly Reduce Alcohol Consumptionmentioning
confidence: 99%
“…Two important variants are long (insertion LL) and short (SS) version. It has been reported in a randomized clinical trial that individuals with LL genotype (Homozygous for the long version) of 5-HTT gene showed significant results in improvements of alcoholism with treatment of ondansetron as compared to LS and SS genotype (Johnson et al, 2011).…”
Section: Genetic Predictors Of Medication Responsementioning
confidence: 99%